2019
DOI: 10.1007/s11192-019-03146-4
|View full text |Cite
|
Sign up to set email alerts
|

The citation advantage of foreign language references for Chinese social science papers

Abstract: Contemporary scientific exchanges are international, yet language continues to be a persistent barrier to scientific communication, particularly for non-native English-speaking scholars. Since the ability to absorb knowledge has a strong impact on how researchers create new scientific knowledge, a comprehensive access to and understanding of both domestic and international scientific publications is essential for scientific performance. This study explores the effect of absorbed knowledge on research impact by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…When there is no incentive to learn and to read documents written in other foreign languages than English, researchers might be motivated to ignore other foreign languages and cite only sources in their native language and in English because it increases their citations. As discussed by Gong et al (2019), Chinese language texts receive more citations when they cite foreign language documents and this foreign language is nearly always English.…”
Section: A = Some Language Other Than Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…When there is no incentive to learn and to read documents written in other foreign languages than English, researchers might be motivated to ignore other foreign languages and cite only sources in their native language and in English because it increases their citations. As discussed by Gong et al (2019), Chinese language texts receive more citations when they cite foreign language documents and this foreign language is nearly always English.…”
Section: A = Some Language Other Than Englishmentioning
confidence: 99%
“…The advantage for those who want to increase their citation count is to cite texts written in English. Gong et al (2019) have shown that Chinese scholars' publications that cite more English-language sources are more cited than publications that cite more sources in Chinese. However, abandoning publishing in a native language and abandoning the citation of sources in non-English languages contribute to the impoverishment of native cultures (Filippov, 2016) and a decrease in cultural diversity.…”
mentioning
confidence: 99%
“…Wesel et al (2014) found that the number of references is significantly related to citations in disciplines like sociology, general and internal medicine and applied physics. Gong et al (2019), on the basis of CSSCI data sources in China, found that for all disciplines, the citation number of papers containing foreign references was significantly higher than that without foreign references. Stevens and Duque (2019) found that when the references were ordered alphabetically, papers rank in the front had a higher possibility of being cited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the existing researches have investigated into factors such as the title of the paper (Guo et al, 2018), its authors (Potthoff and Zimmermann, 2017) and the references (Gong et al, 2019). These types of text have been extensively researched because they are readily accessible and would not require too much computational resources to process.…”
Section: Introductionmentioning
confidence: 99%
“…Результати опитування показують, що автори, для яких англійська мова не є рідною, часто вважають, що рецензенти та редактори журналів упереджені щодо мовленнєвих недоліків у їхніх рукописах [26]. Також, lingua franca може мати негативний ефект на розвиток національних досліджень, що присвячені певним важливим національним питанням, однак є непопулярними серед англомовних досліджень [27]. Кращі перспективи щодо фінансування дослідження, пошуку колег для співпраці, впливовості видань для публікації результатів може стимулювати науковців відмовлятися від регіональної тематики у своїй науковій роботі.…”
Section: важливість вибору мови для публікації результатів досліджень у сгнunclassified